Unveiling Masculinity: A Critical Analysis of Gender Representation in Men's Fragrance Advertisements - Susanto, Danny (Green Publisher Indonesia, 2024)
The aim of this study is to examine how male sexuality is visually portrayed in advertisements for men's perfume and to investigate the notions of masculinity, gender, and sexuality depicted therein. Through a visual text analysis approach rooted in social semiotic theory with literature study, the study examines 27 advertisements predominantly from Western countries (Specifically France and Italy), analyzing elements such as visual composition, gendered representations, and societal implications. The analysis of the sampled images reveals stereotypical representations of male and female sexuality, conveyed through the use of sexuality and gender concepts. For male consumers, exposure to these representations may lead to the internalization of these ideals, influencing their self-image and behavior. These representations not only maintain existing power differentials but also hinder progress towards gender equality and challenging societal norms.